Weight-Related Barriers for Overweight Students in an Elementary Physical Education Classroom: An Exploratory Case Study with One Physical Education Teacher - Odum, Mary; Outley, Corliss W.; McKyer, E. Lisako J.; Tisone, Christine A.; McWhinney, Sharon L. (Frontiers in Public Health, 2017)
Introduction: As physical performance may be more difficult for overweight children than for their non-overweight peers, understanding how weight impacts student performance in the physical education classroom could inform school-based obesity prevention programming. Material and Methods: This qualitative case study examined one elementary physical educator’s perspectives of overweight students’ weight-related experiences in her classroom. Narratives were elicited during an in-depth interview and analyzed using structural and thematic analyses. We utilized the social cognitive theory to inform our exploration of the narratives. Findings: The thematic analysis illuminated a behavioral pattern of student refusal to participate in the physical education classroom while the structural analysis emphasized the teacher’s constructive, individualized responses to participation refusals. Combined, the two analytic techniques provided a more holistic snapshot of the experiences of overweight students in this elementary school. Additionally, a preliminary model explaining the behavioral pattern among overweight students in this particular physical education classroom was created. Discussion: Students who were overweight were more likely to initially refuse to attempt physical tasks in the classroom because they feared peer ridicule, and the teacher played a critical role in whether these students chose to participate in subsequent classes. As agents of change, physical education educators should be included in formative stages of comprehensive, systemic changes to combat childhood obesity. Keywords childhood obesity, elementary school, physical education, qualitative, thematic analysis, structural analysis